THE REACTUALIZATION OF ‘IṢMAH AL-A’IMMAH CONCEPT: Analysis on the Interpretation of al- Ṭabatabâ’î - Suraya Attamimi; Nurhayati Nurhayati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
‘Iṣmah al-a’immah issue has been a polemic among the theology community of Sunni-Shia, particularly in the internal Shia. The Shia Ismâ’ilîyah and Ithnâ ‘Asyarîyah communities believe in the absolute ma’ṣûm character of their leaders/imam. Meanwhile, some Shia Zaidîyah communities limit the character, and the rest totally refuses it. Al-Ṭabatabâ’î, a Shia Ithnâ Asyarîyah ulama known to be moderate and is accepted in Sunni community, has similar opinion with his mazhab’s doctrine regarding ‘iṣmah al-a’immah. However, al- Ṭabatabâ’î tried not to dwell on a never-ending ‘iṣmah issue, but interpreted it contextually instead. This article reveals the ‘iṣmah al-a’immah concept of al- Ṭabatabâ’î by applying qualitative research and analytic descriptive method. According to al- Ṭabatabâ’î, an imam/leader must be ma’ṣûm before guiding people toward devotion. The ma’ṣûm level is achieved through knowledge, irâdah and ikhtiyar of imam in obeying Allah and staying away from immorality. Their obedience makes Allah grant them with a well-absorbed special insight (‘ilm ḥuḍûrî) to form a character that later becomes a self-controller from sinful acts, with which they eventually achieve the ma’ṣûm level. Al- Ṭabatabâ’î then tried to escape from further theological debate by interpreting ‘iṣmah as a potential which is achievable by ordinary people to protect human values.